Praktik Lelang Barang Donasi Masjid dalam Tinjauan Hukum Islam (Studi Kasus Desa Popenga Kecamatan Ulumanda Kabupaten Majene) - Ahmad Syaripudin; Rahmat Rahmat (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2022)
This study aims to determine the legal status of the practice of auctioning mosque donated goods in a review of Islamic law, in Popenga Village, Ulumanda District, Majene Regency. This type of research is qualitative by using inductive/qualitative data analysis, which is to provide a systematic, complete and actual picture of situations and events, regarding the factors and characteristics that influence each other and explain the relationship of the problems being studied. The results of the research show that the auction of goods donated to the mosque in the village of Popenga is to put goods into the mosque with the aim of donating or donating, then auctioned so that the goods are turned into money, thus the funds are used as the cost of building a mosque. The procurement of auctions and transactions like this is prohibited in the mosque because it is not in accordance with Islamic law.